PENGARUH PERSEPSI PENGUSAHA MIKRO KECIL MENENGAH DAN TINGKAT PEMAHAMAN TERHADAP PENGGUNAAN SAK EMKM - Putri Nurfadilah; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACT This study aims to determine the Perception of Small and Medium Entrepreneur and the Use of EMKM IFRSs. The data used in this study are primary data, the study population, namely MSME entrepreneur in the field of food and beverage sampling techniques used purposive sampling method. To provide knowledge material for MSME companies specifically regarding the application of EMKM IFRSs in the preparation of financial statements. The existence of the research is expected to increase the understanding of entrepreneur about financial statements based on SAK EMKM. The result obtained using the multiple linear regression test Y = -0.043+ 0.536 X1 +0.618 X2 and the test from this study using the t test. These result indicate that the Perception of Micro, Small and Medium Entrepreneurs (UMKM) has a positive effect on the use of SAK EMKM and the Level of Understanding does not affect the Use of SAK EMKM.Keyword : Perception, level of understanding, UMKM, SAK EMKM